Trait‐mediated environmental filtering drives assembly at biogeographic transition zones. Issue 4 (1st April 2014) - Sommer, Brigitte; Harrison, Peter L.; Beger, Maria; Pandolfi, John M.
Abstract : Abiotic filtering is a major driver of gradients in the structure and functioning of ecosystems from the tropics to the poles. It is thus likely that environmental filtering is an important assembly process at the transition of biogeographical zones where many species occur at their range limits. Shifts in species abundances and association patterns along environmental gradients can be indicative of environmental filtering, which is predicted to be stronger in areas of high abiotic stress and to promote increased similarity of ecological characteristics among co‐occurring species. Here we test these hypotheses for scleractinian corals along a broad latitudinal gradient in high‐latitude eastern Australia, where corals occur at the margins of their ranges and environmental tolerances. We quantify variation in taxonomic, zoogeographic, and functional patterns combined with null model approaches and demonstrate systematic spatial variation in community structure and significant covariance of species abundance distributions and functional characteristics along the latitudinal gradient. We describe a strong biogeographic transition zone, consistent with patterns expected under abiotic filtering, whereby species are sorted along the latitudinal gradient according to their tolerances for marginal reef conditions. High‐latitude coastal reefs are typified by widely distributed, generalist, stress‐tolerant coral species with massive and horizontally spreading morphologies and by diminishing influence of tropical taxa at higher latitudes and closer to the mainland. Higher degree of ecological similarity among co‐occurring species than expected by chance supports the environmental filtering hypothesis. Among individual traits, the structural traits corallite size and colony morphology were filtered most strongly, suggesting that characteristics linked to energy acquisition and physical stability may be particularly important for coral survival in high‐latitude environments. These findings highlight interspecific differences and species interactions with the environment as key drivers of community organization in biogeographic transition zones and support the hypothesis that environmental filters play a stronger role than biotic interactions in structuring ecological communities in areas of high abiotic stress.